Book review: Furtado, Celso (2020): The myth of economic development, Medford, MA, USA and Cambridge, UK (111 pages, Polity Press, hardcover, ISBN 978-1-5095-4013-6; softcover, ISBN 978-1-5095-4014-3; ebook, ISBN 978-1-5095-4015-0) - Graña Colella, Santiago (2021)
On the 100th anniversary of Celso Furtado's birth, several publications, such as Klüger (2020) and Lacerda et al. (2020), and conferences, such as 'Celso Furtado 100 anos', were created to honour the achievements of one of the founders of Latin American Structuralism. In this context, Polity Press has published, for the first time in English, Furtado's book from 1974, O Mito do Desenvolvimento Econômico. In this book, Furtado aims to unmask what he names as 'the myth of economic development', which acts as guidance for most economic models of development. In short, the myth consists of the belief that consumption patterns from central countries, associated with development, can be universalized to the entire population of undeveloped peripheral countries. To elaborate on his arguments, Furtado critically revises 'The limits to growth' (LTG) report (Meadows et al. 1972), commissioned by the club of Rome. This study concluded, by means of a computational model, that the world seen as a whole system would find its limits to growth approximately 100 years after the publication of the LTG report. According to Furtado, this report, which has had great influence in the de-growth literature (Fournier 2008), is wrongly based on the myth of economic development and consequently overestimates the consequences of growth, leading to 'catastrophic conclusions'. The English version of O Mito do Desenvolvimento Econômico analysed in the present review includes an introduction by Ndongo Samba Sylla, which presents a short biography of Furtado focusing on his academic influences and studies, publications, and research framework. In addition, the introduction provides a summary of the LTG report and a summary and analysis of The Myth of Economic Development itself.